2021
DOI: 10.1021/acs.jafc.1c01006
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic Recognizer-Assisted Homogeneous Electrochemiluminescence Determination of Organophosphorus Pesticides via Target-Controlled Emitter Release

Abstract: Given the relevance of organophosphorus pesticides (OPs) with food safety, it is highly urgent to develop sensitive and reliable sensors for OPs. However, most of the OP sensors are developed based on colorimetric and fluorescent techniques, which are limited to severe interference of color and fluorescence from pigments and organic acids in agricultural crops. Herein, we develop an inorganic recognizer-based homogeneous electrochemiluminescence (ECL) sensor for the highly sensitive and credible determination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…Organophosphorus pesticides, such as paraoxon, diazinon, chlorpyrifos, fenitrothion, etc., have been proven to be harmful for the aquatic organisms and mammal animals, especially for the pregnant women and children. [1][2][3] The structures of these organophosphorus pesticides are illustrated in Scheme 1. Among them, the widely-used paraoxon (PON) and parathion (PIN) have relatively strong toxicity to the inactivation of mammalian acetylcholinesterase (AChE) by phosphorylating a serine residue in the active site of AChE.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Organophosphorus pesticides, such as paraoxon, diazinon, chlorpyrifos, fenitrothion, etc., have been proven to be harmful for the aquatic organisms and mammal animals, especially for the pregnant women and children. [1][2][3] The structures of these organophosphorus pesticides are illustrated in Scheme 1. Among them, the widely-used paraoxon (PON) and parathion (PIN) have relatively strong toxicity to the inactivation of mammalian acetylcholinesterase (AChE) by phosphorylating a serine residue in the active site of AChE.…”
Section: Introductionmentioning
confidence: 99%
“…Organophosphorus pesticides, such as paraoxon, diazinon, chlorpyrifos, fenitrothion, etc., have been proven to be harmful for the aquatic organisms and mammal animals, especially for the pregnant women and children [1–3] . The structures of these organophosphorus pesticides are illustrated in Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“…These superior properties permit them on various sensing mechanisms, including optical sensation through chemiluminescence, surface plasmon resonance (SPR), and electrochemistry for a field-effect transistor (FET, voltage-current under gating control) by p-n junctions for detecting specific biomolecules and gases [54,58,59]. For instance, 2D Mn oxides-based materials exhibit a powerful catalytic property that has been employed as nanoenzymes for catalyzing the hydrolysis of biomolecules via peroxidase-like activity, thereby producing electrochemical/electrochemiluminescence signals as the detection readouts [60][61][62]. While metal oxides may play a more critical role in chemical catalysis and fuel cells, TMDs can be a significant part of sensor developments [63,64].…”
Section: Two-dimensional Nanocompositesmentioning
confidence: 99%
“…A high concentration of acetylcholine is thought to be responsible for the intense cholinergic effects that may include muscle weakness, muscle twitching, sensory and behavioral disturbances (Parkinson's, Alzheimer's) [6], motor function impairments, and respiratory depression (EPA 2013) [7]. Previous studies have reported several methods for the detection of pesticides, immunoassay [8,9], electrochemiluminescence biosensor [10,11], gas chromatography-mass spectrometry (GC-MS) [12,13], and high-performance liquid chromatography (HPLC) [14,15]. However, these methods lack behind by lengthy sample preparation, low recovery, and reproducibility, limiting their utility as diagnostic tools.…”
Section: Introductionmentioning
confidence: 99%